Shock and awe: Distinct effects of taboo words on lexical decision and free recall. Issue 4 (3rd April 2017) - Madan, Christopher R.; Shafer, Andrea T.; Chan, Michelle; Singhal, Anthony
ABSTRACT: Taboo stimuli are highly arousing, but it has been suggested that they also have inherent taboo-specific properties such as tabooness, offensiveness, or shock value. Prior studies have shown that taboo words have slower response times in lexical decision and higher recall probabilities in free recall; however, taboo words often differ from other words on more than just arousal and taboo properties. Here, we replicated both of these findings and conducted detailed item analyses to determine which word properties drive these behavioural effects. We found that lexical-decision performance was best explained by measures of lexical accessibility (e.g., word frequency) and tabooness, rather than arousal, valence, or offensiveness. However, free-recall performance was primarily driven by emotional word properties, and tabooness was the most important emotional word property for model fit. Our results suggest that the processing of taboo words is influenced by distinct sets of factors and by an intrinsic taboo-specific property.